THE ASSESSMENT OF THE INVESTMENT EFFICIENCY OF RUSSIAN SOVEREIGN WEALTH FUNDS - Ye. A. Vasin (Финансы: теория и практика, 2017)
The activity of Russian sovereign wealth funds draws special attention of the international investment community due to the scale and social and economic significance of their investments. The need in the objective assessment of the investment efficiency of sovereign wealth funds arose as early as at the time of establishment in Russia of the first sovereign fund. This article presents the results of the analysis of investment policy statements of such funds, as well as an assessment of the investment efficiency of Russian sovereign wealth funds according to the criterion of investment returns maximization at an acceptable risk level. The analysis of the investment efficiency of the Russian Federation Stabilization Fund, the Reserve Fund and the National Welfare Fund was carried out by the author using state-of-the-art investment evaluation methods such as the investment portfolio benchmarking, VaR analysis. The analysis revealed a number of flaws in the current organizational structure of sovereign fund management as well as factors retarding the effective fund value growth. Based on the results obtained, a set of organizational and methodological measures was proposed to increase the investment efficiency of the Reserve Fund and the National Welfare Fund